2023
DOI: 10.1017/s0029665123000022
|View full text |Cite
|
Sign up to set email alerts
|

Promoting and disseminating consistent and effective nutrition messages: challenges and opportunities

Abstract: Nutrition messages are a central part of policy making as well as communication via product information, advertising, healthcare advice and lifestyle campaigns. However, with amplified information (and misinformation) from a growing number of sources, inconsistent and conflicting food landscapes, and limited engagement from the public, nutrition messaging tensions have become more accentuated than previously. In this review, we focus on the challenges facing those wishing to effect dietary change through commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Students also mentioned easiness into daily routine as a dominant driver of modulating sustainable behaviour. This finding supports previous research which highlighted that individuals are more likely to engage in educational messaging if there are clear benefits, it is easy to implement, and resonates [44]. Thus, our paper provides key design pointers for students; accordingly, next steps should involve implementing such cues as well as investigating the impact of educational materials on students' behaviour over both the short and long term in ecological valid settings (e.g., household and/or on-the-go).…”
Section: Discussionsupporting
confidence: 90%
“…Students also mentioned easiness into daily routine as a dominant driver of modulating sustainable behaviour. This finding supports previous research which highlighted that individuals are more likely to engage in educational messaging if there are clear benefits, it is easy to implement, and resonates [44]. Thus, our paper provides key design pointers for students; accordingly, next steps should involve implementing such cues as well as investigating the impact of educational materials on students' behaviour over both the short and long term in ecological valid settings (e.g., household and/or on-the-go).…”
Section: Discussionsupporting
confidence: 90%
“…held more misinformed views across all 25 statements ( Figure 2 ). Aside from these sources being commonly held responsible for spreading misinformation and for amplified misinformation vulnerability [ 1 , 15 , 136 , 137 , 138 , 139 , 140 , 141 ], personal factors such as lower levels of health literacy cannot be discounted [ 142 , 143 ]. Research has indicated that individuals with health literacy deficiencies are more prone to use non-scientific sources such as television, social media, blogs, or celebrity webpages [ 144 , 145 ] and more susceptible to health misinformation [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of diet-nutrition information sources in today's digital era has brought both opportunities and challenges. While access to information has increased, so has the prevalence of misinformation and misleading claims regarding diet and nutrition [1,2]. Understanding how individuals navigate this landscape of information and evaluate the trustworthiness of sources is crucial for combating the risks associated with misinformation and potentially ill-informed dietary decisions with harmful health consequences [1].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of misinformation in this domain extend beyond individual health outcomes, impacting public health, healthcare systems, and societal well-being [5,[12][13][14][15]. Recognizing the prevalence and problems associated with misinformation in diet and nutrition is crucial for fostering informed decision making, promoting evidence-based practices, and addressing the risks and implications of false information and wrongful advice on public health [2].…”
Section: Introductionmentioning
confidence: 99%